1977
DOI: 10.1037/0022-3514.35.9.677
|View full text |Cite
|
Sign up to set email alerts
|

Self-reference and the encoding of personal information.

Abstract: The degree to which the self is implicated in processing personal information was investigated. Subjects rated adjectives on four tasks designed to force varying kinds of encoding: structural, phonemic, semantic, and self-reference. In two experiments, incidental recall of the rated words indicated that adjectives rates under the self-reference task were recalled the best. These results indicate that self-reference is a rich and powerful encoding process. As an aspect of the human information-processing system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

76
1,162
6
16

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,479 publications
(1,283 citation statements)
references
References 15 publications
76
1,162
6
16
Order By: Relevance
“…The most popular explanation of the SRE is that SR promotes elaborative processing of to-be-remembered information (Keenan, 1993;Rogers et al•, 1977)• Based on DOP theory, depth is equated with the extent or amount of processing that a stimulus receives, whereas elaboration involves item-specific processing (see Eysenck & Eysenck, 1979)• When a participant processes a word using elaboration, he or she attends to the specific meaning of the word and the semantic associations between the word and extra list material in semantic memory (Anderson & Reder, 1979;Einstein & Hunt, 1980;Klein & Loftus, 1988). According to Klein and Loftus, the effect of this kind of processing is to provide multiple routes for retrieval and create an environment in which "inference-based reconstruction .…”
Section: Self As a Cognitive Construct That Promotes Elaborationmentioning
confidence: 99%
See 2 more Smart Citations
“…The most popular explanation of the SRE is that SR promotes elaborative processing of to-be-remembered information (Keenan, 1993;Rogers et al•, 1977)• Based on DOP theory, depth is equated with the extent or amount of processing that a stimulus receives, whereas elaboration involves item-specific processing (see Eysenck & Eysenck, 1979)• When a participant processes a word using elaboration, he or she attends to the specific meaning of the word and the semantic associations between the word and extra list material in semantic memory (Anderson & Reder, 1979;Einstein & Hunt, 1980;Klein & Loftus, 1988). According to Klein and Loftus, the effect of this kind of processing is to provide multiple routes for retrieval and create an environment in which "inference-based reconstruction .…”
Section: Self As a Cognitive Construct That Promotes Elaborationmentioning
confidence: 99%
“…SR-semantic and SR-OR comparisons. Given the foregoing logic, we expected the results of our investigation to show that SR should produce superior memory when compared with tasks that promote less elaboration. Proponents of the elaboration hypothesis argued that, under most circumstances, SR results in greater elaboration of the stimulus word than that achieved by a semantic comparison task (e.g., Rogers et al, 1977). Thus, based on the elaboration hypothesis, the SRE should be smaller (or disappear altogether) when studies use semantic-encoding tasks that engender greater elaboration and larger when the semantic-encoding tasks engender less elaboration than the SR.…”
Section: Self As a Cognitive Construct That Promotes Elaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in these studies, retrieval performance is better for information that has been encoded in reference to the self than for information that has been processed semantically or in reference to other people. This wellknown cognitive phenomenon, named the Self Reference Effect (SRE; Rogers et al, 1977), is a strong characteristic of human cognition since it has been observed in various populations including healthy older people (Gutchess et al, 2007), with various materials and various paradigms at encoding and recognition and with different designs (for a review see Symons and Johnson, 1997).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The SRE is the beneficial effect of encoding material with reference to oneself and is consistent with a functionally distinct memory system for self-knowledge. One of the first studies to report an SRE was by Rogers et al (1977). They compared memory for adjectives in four experimental conditions, in which the subject was asked to judge (a) the size of the letters that made up the word, (b) whether the word rhymed with another word, (c) whether the word was a synonym for another word, or (d) whether the word described the subject.…”
Section: Traitsmentioning
confidence: 99%